1994
DOI: 10.1021/la00020a009
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering by Agglomerates: Coupled Electric and Magnetic Dipole Method

Abstract: The coupled electric dipole method (CEDI for treating light scattering by an agglomerate particle is extended to include both the electric and magnetic dipole terms (CEMD). The accuracy of these two methods along with the Rayleigh-Debye (RD) method is obtained by comparing with the exact solution for two spheres in contact. It is found that addition of the magnetic dipole term extends the range of the coupled dipole method from a primary sphere diameter of about 0.06 pm to about 0.12 pm for sootlike particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
151
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 0 publications
1
151
2
Order By: Relevance
“…Even so, previous studies showed that RDG in general produces reasonably accurate results for the scattering properties of soot (Dobbins and Megaridis 1991;Farias et al 1996). Multiple scattering within a fractal aggregate was found small in several studies (Berry and Percival 1986;Singham and Bohren 1993;Mulholland et al 1994;Farias et al 1996).…”
Section: Rayleigh-debye-gans Fractal Aggregate Theorymentioning
confidence: 95%
“…Even so, previous studies showed that RDG in general produces reasonably accurate results for the scattering properties of soot (Dobbins and Megaridis 1991;Farias et al 1996). Multiple scattering within a fractal aggregate was found small in several studies (Berry and Percival 1986;Singham and Bohren 1993;Mulholland et al 1994;Farias et al 1996).…”
Section: Rayleigh-debye-gans Fractal Aggregate Theorymentioning
confidence: 95%
“…Soot carbon is composed of primary spherules with radii R p 0.025 µm that are aggregated with other spherules into large particles, and the resulting agglomerates look like chains of spheres with multiple branches (hence the term "chain aggregates;" Li et al, 2003a, b;Wentzel et al, 2003;Chakrabarty et al, 2006;Adachi et al, 2010;Wu et al, 2012;Chakrabarty et al, 2013). The absorption cross section for the aggregated particles can be reasonably modeled as a collection of the primary sC spheres, even though the agglomerates have complex shapes (Mulholland et al, 1994;Fuller, 1995;Farias et al, 1996;Fuller et al, 1999;Sorensen, 2001;Schnaiter et al, 2003;Chakrabarty et al, 2007;Liu et al, 2008;Chung et al, 2012a). Thus, the primary spherule size is the appropriate length scale for determining AAE (Bergstrom et al, 2002), and externally mixed sC aggregates occupy the parameter space highlighted by the maroon rectangle in the upper left of Fig.…”
Section: Aae For Spectrally Invariant Kmentioning
confidence: 99%
“…When the feature size of the high refractive index dielectric nanoparticles is significantly smaller than the incident wavelength, the resulting optical resonance can be described by the effective electric dipole and magnetic dipole as [32]:…”
Section: Theoretical Modal Of Coupled Nanoparticlesmentioning
confidence: 99%
“…When considering the interaction between multiple nanoparticles, the electric and magnetic fields at the ith particle, as caused by the jth particle, can be represented by [32] …”
Section: Theoretical Modal Of Coupled Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation